Storm catchers - Bowler, Tim (Margaret K. McElderry Books, 2001)
Fin is devastated by guilt when his sister, Ella, is kidnapped, snatched away from the house in the middle of a storm. As the kidnappers make their demands, Fin's guilt is replaced by a fierce determination to find his sister by whatever means he can, and bring the criminals to justice. But as the drama unfolds, a complex web of family secrets is revealed